2017
DOI: 10.3389/fmicb.2017.01402
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Polyphleates, External Cell Wall Lipids in Mycobacterium abscessus, Are Associated with the Formation of Clumps with Cording Morphology, Which Have Been Associated with Virulence

Abstract: Mycobacterium abscessus is a reemerging pathogen that causes pulmonary diseases similar to tuberculosis, which is caused by Mycobacterium tuberculosis. When grown in agar medium, M. abscessus strains generate rough (R) or smooth colonies (S). R morphotypes are more virulent than S morphotypes. In searching for the virulence factors responsible for this difference, R morphotypes have been found to form large aggregates (clumps) that, after being phagocytozed, result in macrophage death. Furthermore, the aggrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…It is also possible that trehalose analogues could act on other metabolic pathways that utilize trehalose, such as the production of extracellular glucans or trehalose polyphleates, which are not required for growth but could be constituents of the biofilm extracellular matrix. [5, 39, 40]…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that trehalose analogues could act on other metabolic pathways that utilize trehalose, such as the production of extracellular glucans or trehalose polyphleates, which are not required for growth but could be constituents of the biofilm extracellular matrix. [5, 39, 40]…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it would be interesting to study the glycolipids level in response to MB. Since MTB comprises unique cell envelope components due to the presence of complex lipids that render its drug resistance and pathogenicity [ 20 ], altered cell surface phenotypes due to MB are crucial as they may lead to modifications in the cell wall components that could in turn affect cell interactions and various other linked attributes. Further intricate studies are needed to find the reasons for the observed defects in phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…These MmpLs represent the only MmpL actors described so far in M. abscessus virulence, despite the greater abundance of MmpLs in the M. abscessus complex (4). Another group of lipids, the trehalose-based polyphleates, present in many NTM (37) has recently been proposed to contribute to the highly aggregative phenotype of M. abscessus R (38), but a direct role in M. abscessus virulence remains to be shown.…”
Section: Significancementioning
confidence: 99%